Molten Salt Synthesis of SrTi0.95Fe0.05O3: The Effect of Chloride Salt Type Study - Pertiwi, Ulvi Dwi; Anwari, Nelly Safitri; Safitri, Widiya Nur; Pramono, Edi; Prasetyo, Anton (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2025)
Strontium titanate (SrTiO3) refers to a perovskite structure compound reported to have photocatalyst properties. It is well-known that modifying the particle morphology is found to be capable of enhancing the photocatalytic activity as it can increase the reaction sites on the solid surface. Molten salt synthesis is one of the compound synthesis methods to produce the homogeneous particle size as well as the unique morphology. One of the parameters determining the product compound obtained using the molten salt method is the type of salt used. In this study, the SrTi0.95Fe0.05O3 was synthesized by the molten salt method using NaCl, KCl, and NaCl/KCl salt. It also studied the effects of chloride salt type to structure, vibration mode, morphology particle, band gap energy, and thermal stability of product samples. The diffractograms showed that SrTi0.95Fe0.05O3 were successfully synthesized; however, the sample obtained using molten KCl salt had the impurities of TiO2, and SrCO3 (residual of precursors) indicating that the KCl flux was insufficient to make a complete reaction. The characteristic of infrared vibration modes of the SrTiO3 compound were found in all samples. The image of scanning electron microscopy showed that all particle morphology was in the quadrate-particle shape, and the SrTi0.95Fe0.05O3-KCl sample had the smallest particles for having the largest surface area. The Kubelka-Munk equation calculation results showed that all samples’ band gap energy was approximately at ∼3 eV. The DSC curve showed a relatively similar pattern; therefore, the thermal stability properties of all samples were similar.